Prevalence of Anemia and Associated Factors among Pregnant Women in an Urban Area of Eastern Ethiopia - Kefyalew Addis Alene; Abdulahi Mohamed Dohe (Anemia)
This research work presents the magnitude of anemia and its determinant factors among pregnant women. As far as this research is done in the eastern part of Ethiopia, where there is a different cultural issue related to pregnancy and dietary habit, it will help the researchers to know the problem in different parts of the country.